Perencanaan Full Day School Dalam Pembinaan Keagamaan Peserta Didik di SMK Negeri 5 Telkom Banda Aceh - Sari, Era Novita; Nurmayuli, Nurmayuli (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2023)
The implementation of full day school really helps the school in maximizing practicum time for students. However, it is still found that worship facilities are inadequate, which of course affects the full day program at the school. This research was conducted to determine the planning of full day school in the religious formation of students at SMK Negeri 5 Telkom Banda Aceh. This research is field research using qualitative methods. The data collection techniques used were observation, interviews and documentation. The research subjects included curriculum representatives, PAI teachers and students. The results of this research show that full day school planning in the religious development of students at SMK Negeri 5 Telkom Banda Aceh includes (1) Planning in the dimensions of religious worship and practice which includes theoretical development of PAI subjects, extracurricular Koran reading, and midday prayers in congregation. (2) Planning in the dimensions of experience and consequences includes the development of PAI theory practice, academic and non-academic extracurriculars, and coaching to read the Al-Quran every day as well as the reading of Surah Yasin and Tausiah on Fridays. (3) Planning is carried out at the beginning of each semester in open deliberation involving all teaching and educational staff so that implementation in one semester can run effectively and efficiently as expected.